Revision of the Neotropical burrowing water beetle genus Liocanthydrus Guignot (Coleoptera: Noteridae: Noterinae: Noterini) with the description of two new species - Baca, Stephen M.; Gustafson, Grey T.; Toledo, Mario; Miller, Kelly B. (Zootaxa, 2014)
The burrowing water beetle genus Liocanthydrus Guignot, 1957 is redefined and its species are revised. Of the four current species, three are recognized as belonging to the genus and redescribed: L. angustus (Guignot, 1957), L. octoguttatus (Zimmermann, 1921) and L. uniformis (Zimmermann, 1921). The fourth species, L. buqueti (Laporte, 1835) is found to not be a member of Liocanthydrus, but of an undescribed genus. The noterid genus Siolius J. Balfour-Browne, 1969, is synonymized with Liocanthydrus (new synonymy) based on comparison of type specimens in both groups. Two of the three species described in Siolius, S. bicolor J. Balfour-Browne, 1969 and S. clayae J. Balfour-Browne, 1969, are recognized as valid, transferred to Liocanthydrus, and redescribed. The third, S. amazonicus J. Balfour- Browne, 1969, is synonymized with L. uniformis (new synonymy). Two new species from South America, L. armulatus sp. n. and L. nanops sp. n. are also recognized and described. A lectotype is designated for Canthydrus octoguttatus Zimmermann, 1921. After this revision, there are seven valid species of Liocanthydrus. Habitus photos are provided, diagnostic characters of all recognized species are illustrated, distributions are provided, and a key to the species is included.